Programas de capitalizacion de la deuda externa en America Latina (Instituto Interamericano de Mercados de Capital CaracasVE, 1987)
Describes characteristics of debt for equity programs in Latin America. Examines their costs, benefits, limitations, and difficulties. Gives a detailed analysis of programs established in Chile, Mexico, Ecuador and Venezuela, as well as the preliminary arrangements for a similar program in Brazil. Makes preliminary conclusions based on the experience gained from debt for equity programs.
IDS